2022
DOI: 10.1021/acsfoodscitech.1c00390
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Compound Oleogels Based on Monoglycerides and Edible Waxes

Abstract: A combination of different gelators provides a pursuable way to create oleogels with enhanced properties. In this work, high oleic sunflower oil was structured using monoglycerides (MGs), waxes (carnauba wax, beeswax, candelilla wax, rice bran wax), and their mixtures, aiming at investigating the effects of compounding MG with wax on microstructures, the gelation process, and physicochemical and digestion properties of resultant oleogels. Compounding MG with wax leads to different oleogel properties of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The GsC and ratio affected the formation of the three‐dimensional network at the end of the cooling step ( P < 0.01) (Table 3). Before the holding stage, due to the formation of non‐homogeneous and large‐size crystals, 12 G ′ reached 58% and 64% of its final values for D 100 ‐50 and D 100 ‐100, respectively, which were the lowest values at concentrations of 50 and 100 g kg −1 . Apart from D 100 ‐100, during the holding stage, the maximum change in the G ′ value of oleogels, prepared at a concentration of 100 g kg −1 , was 10%, which indicated that, because of the accelerated nucleation at higher gelators' mass, the network formation was nearly finished in this concentration.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The GsC and ratio affected the formation of the three‐dimensional network at the end of the cooling step ( P < 0.01) (Table 3). Before the holding stage, due to the formation of non‐homogeneous and large‐size crystals, 12 G ′ reached 58% and 64% of its final values for D 100 ‐50 and D 100 ‐100, respectively, which were the lowest values at concentrations of 50 and 100 g kg −1 . Apart from D 100 ‐100, during the holding stage, the maximum change in the G ′ value of oleogels, prepared at a concentration of 100 g kg −1 , was 10%, which indicated that, because of the accelerated nucleation at higher gelators' mass, the network formation was nearly finished in this concentration.…”
Section: Resultsmentioning
confidence: 98%
“…The lowest and highest γ L values were found for DMG and CBW oleogels, respectively, implying that DMG oleogels were more flexible 24 and CBW oleogel had high stability under the strain sweep test 25 . The differences in crystal nature of CBW and DMG, the homogeneous and small‐size crystals versus the non‐homogeneous and large‐size crystals, lead to fewer contact sites, loose entanglement of crystals, and, subsequently, higher deformability of the DMG oleogel 12,22 . On the other hand, as a result of the denser crystal network, CBW oleogel demonstrated the highest G ′ LVR , τ yLVR , and τ f values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that Van der Waals and electrostatic interactions contribute to the gelation of edible oils in addition to hydrogen bonds and stacking interactions. Oleogels are generally prepared by adding gelators to edible oil and then treating them with thermal processing [ 9 ]. However, recent research has found that ultrasonication can improve the gelling property of oleogels.…”
Section: Introductionmentioning
confidence: 99%